Victimization and Perpetration of Online Dating Violence and Emotional Dependence by Gender among University Students in Ecuador - Mayra Castillo-Gonzáles; Emilio Terán Andrade (Social Sciences, 2024)
The present study investigates the roles of online dating violence and emotional dependence within the context of interpersonal relationships. The primary objective of this research is to analyze the perpetration and victimization of online dating violence and emotional dependence among men and women. Utilizing a quantitative approach with a descriptive and explanatory focus, this research employed a non-experimental cross-sectional design. A sample comprising 3202 university students completed the Dating Online Abuse Scale (DOAS) and the Emotional Dependence Questionnaire (EDQ). Statistical analyses, including Student’s t-test, Pearson’s correlation coefficient, and simple linear regressions, were conducted. Significant gender differences (p < 0.01) emerged concerning both victimization and perpetration of online dating violence. Furthermore, a noteworthy association (p < 0.01) was observed between online dating violence and emotional dependence, with the latter serving as a predictive factor for online dating violence across genders.